Pelatihan Transmisi Otomatis Untuk Meningkatkan Kesiapan Mengajar - Marji Marji; Komarudin Komarudin; Imam Muda Nauri; Erwin Komara Mindarta (Universitas Negeri Malang, 2023)
The automotive development sector especially transmission shifts. That challenge for VocationalHigh Schools (SMK) which graduated technician candidates. For long time ago car transmissionswere dominated used manual transmissions, currently automatic transmissions (AT) dominatedover manual transmissions. One of the causes were used AT was traffic jams. Based on the resultsof interviews with teachers and students, information was obtained that (1) many vocational schoolteachers did not master automatic transmission material; (2) vocational school students did nothad the competency to maintain car automatic transmissions; (3) many vocational schools hadautomatic transmissions but ware not used. Participants in this training were 30 vocational schoolteachers in Malang district. The material presented in this research was the Suzuki Swift 4-speedautomatic transmission. This study used a quantitative approach. The training program evaluationmethod used in this research is the Kirkpatrick Four Levels Evaluation Model. Based on the resultsof the questionnaire, it shows that the facilities used in this training are as desired. The Anova testresults show a significance of 0.00, which means that there is a significant difference between thepretest and posttest. Automatic transmission training is effective for improving automatictransmission maintenance competency